Tax-motivated profit shifting in big 4 networks: Evidence from Europe - Elemes, Anastasios; Blaylock, Bradley; Spence, Crawford (Accounting, Organizations and Society, 2021)
Accounting research on tax has primarily focused on documenting the income shifting strategies of multinational corporations. However, no studies, as far as we are aware, have hitherto explored how large accountancy firms manage their own tax affairs despite being huge economic entities in their own right. Using a unique private firm dataset of Big 4 affiliated firms from 30 European countries we examine whether the Big 4 shift income among their separate legal entities. Despite apparent disincentives to doing so, we find archival evidence consistent with tax-motivated income shifting. Difference-in-difference specifications around the incorporation of Deloitte EMEA in the U.K. and PwC Europe in Germany provide further evidence consistent with income shifting increasing among Deloitte and PwC affiliates subsequent to the incorporation of their respective regional coordinating entities. In cross-sectional analyses we find evidence consistent with incentives to engage in outbound income shifting being weaker for unprofitable affiliates. We also provide evidence consistent with the Big 4 engaging in income shifting only in countries with favourable tax conditions/weak tax enforcement. Finally, we find evidence in line with debt allocation and intangible asset placement being important channels through which the Big 4 achieve their income shifting objectives. Our study contributes to the literature by being the first to open the black box of the Big 4's own tax planning practices.